Local Business Taxation and Competition for Capital: The Choice of the Tax Rate - Thiess Büttner (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1998)
This paper discusses how local tax rates of the business tax are set when communities compete for capital as a mobile factor. In a theoretical model communities provide public inputs financed by a tax on capital income in order to maximize a general objective function, which includes residents' income but also the tax revenue. It is shown that irrespective of the actual weights in the objective functions, the communities will respond to each others taxing decisions. However, in the tax equilibrium differences in tax rates are not eliminated if communities differ in size or in the councils' preferences. These propositions are then related to the empirical distribution and development of the statutory collection rates of the business tax in West Germany's districts. The results indicate that collection rates are set in response to the fiscal decisions of local neighbors. Yet, competition does not eliminate all tax differences between locations, since tax rates are positively related to the population size of districts, whereas only weak density effects are found. This indicates that large jurisdictions are less exposed to tax competition.
Keywords: 330; fiscal competition; capital income taxation; public inputs; local taxation; empirical study; spatial effects